2022
DOI: 10.1097/icl.0000000000000931
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Two Extended Depth of Focus Intraocular Lenses

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…The results of our study also showed that both Symfony ® and Synergy ® had better visual outcomes compared to those in previous studies for intermediate vision, with Symfony ® showing slightly better visual outcomes than Synergy ® without statistical significance [26]. Previous studies have reported UNVA values in the range of 0.27 ± 0.11 to 0.41 ± 0.09 [9,27,28] for Symfony ® and 0.04 ± 0.09 to 0.10 ± 0.07 for Synergy ® [17,22]. CNVA values were reported in the range of 0.33 ± 0.11 to 0.16 ± 0.15 for Symfony ® [18,23,25] and 0.03 ± 0.11 to 0.00 ± 0.03 for Synergy ® [8,18].…”
Section: Discussionsupporting
confidence: 72%
“…The results of our study also showed that both Symfony ® and Synergy ® had better visual outcomes compared to those in previous studies for intermediate vision, with Symfony ® showing slightly better visual outcomes than Synergy ® without statistical significance [26]. Previous studies have reported UNVA values in the range of 0.27 ± 0.11 to 0.41 ± 0.09 [9,27,28] for Symfony ® and 0.04 ± 0.09 to 0.10 ± 0.07 for Synergy ® [17,22]. CNVA values were reported in the range of 0.33 ± 0.11 to 0.16 ± 0.15 for Symfony ® [18,23,25] and 0.03 ± 0.11 to 0.00 ± 0.03 for Synergy ® [8,18].…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies [ 2 , 22 , 24 , 25 , 26 ] have also demonstrated the effect of mini-monovision with a non-diffractive EDOF, Vivity IOL. While some recent studies have compared the bilateral implantation of the Vivity IOL with emmetropia and trifocal IOL, other types of EDOF IOL, or Monofocal IOL [ 12 , 27 , 28 , 29 , 30 , 31 , 32 ], our study compared the clinical outcomes of the Vivity IOL with mini-monovision trifocal and monofocal IOLs. This study showed that the bilateral implantation of a Vivity IOL with mini-monovision was beneficial for near- and intermediate-vision, with high patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%